2021
DOI: 10.1021/acsanm.1c02087
|View full text |Cite
|
Sign up to set email alerts
|

Activity–Composition Relationships of Fe–Ni–Cu Ternary Nanoparticles Supported on Al2O3 as Three-Way Catalysts for NO Reduction

Abstract: Ternary Fe x Ni y Cu 1−x−y (x, y: molar fractions) metal nanoparticles supported on Al 2 O 3 were prepared by H 2 -reduction treatment at 900 °C and investigated as three-way catalysts free of precious metals (Rh, Pd, and Pt). As-prepared nanoparticles consisted of nearly homogeneous alloys, whereas their surfaces were partially oxidized. Further oxidation occurred upon exposure to a reaction gas mixture (NO−CO−C 3 H 6 −O 2 −H 2 O) at lower temperatures of ≤400 °C. At higher temperatures, however, Cu and Ni re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Considering the 1:2 ratio of NiFe 2 O 4 , the remaining Ni may be in the form of CuNi alloy, as shown in Figure . Previously, we reported a similar structural change that occurred in the ternary FeNiCu catalyst when exposed to the reaction gas mixture . Based on these characterization results, the local structural change under the catalytic reaction condition is schematically inferred, as illustrated in Scheme .…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…Considering the 1:2 ratio of NiFe 2 O 4 , the remaining Ni may be in the form of CuNi alloy, as shown in Figure . Previously, we reported a similar structural change that occurred in the ternary FeNiCu catalyst when exposed to the reaction gas mixture . Based on these characterization results, the local structural change under the catalytic reaction condition is schematically inferred, as illustrated in Scheme .…”
Section: Resultsmentioning
confidence: 57%
“…The Cu metal surface favors nondissociative NO adsorption, but it also catalyzes NO reduction by dimerizing two NO molecules to form ONNO, followed by the N–O bond cleavage to form N 2 . , The Cu metal surface’s activity can further be modified by a combination with other transition metals. A NiCu alloy is one such case showing superior catalytic performance for NO reduction, as revealed by several research groups. ,, Tanaka et al and Asakura et al ,, reported the higher catalytic activity of NiCu compared to its monometal counterparts. Papanikolaou and Stamatakis successfully demonstrated the NiCu surface’s catalytic activity in the NO–CO reactions using density functional theory combined with microkinetic modeling.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Various types of PGM-free catalysts have been proposed so far [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], however, the low NO reduction activities are the serious problems in base metal oxide catalysts. For example, although NiFe 2 O 4 showed the highest NO reduction activity among base metal oxide-based TWC catalysts, the rate of NO reduction was only 1/8 of that of Rh/ZrO 2 [27].…”
Section: Introductionmentioning
confidence: 99%